Drosophila arginine methyltransferase 1 (DART1) is an ecdysone receptor co-repressor. - Kimura, S.; Sawatsubashi, S.; Ito, S.; Kouzmenko, A.; Suzuki, E.; Zhao, Y.; Yamagata, K.; Tanabe, M.; Ueda, T.; Fujiyama, S.; Murata, T.; Matsukawa, H.; et al. (Biochemical and Biophysical Research Communications, 2008)
Histone arginine methylation is an epigenetic marker that regulates gene expression by defining the chromatin state. Arginine methyltransferases, therefore, serve as transcriptional co-regulators. However, unlike other transcriptional co-regulators, the physiological roles of arginine methyltransferases are poorly understood. Drosophila arginine methyltransferase 1 (DART1), the mammalian PRMT1 homologue, methylates the arginine residue of histone H4 (H4R3me2). Disruption of DART1 in Drosophila by imprecise P-element excision resulted in low viability during metamorphosis in the pupal stages. In the pupal stage, an ecdysone hormone signal is critical for developmental progression. DART1 interacted with the nuclear ecdysone receptor (EcR) in a ligand-dependent manner, and co-repressed EcR in intact flies. These findings suggest that DART1, a histone arginine methyltransferase, is a co-repressor of EcR that is indispensable for normal pupal development in the intact fly.